The gut as a lymphoepithelial organ: the role of intestinal epithelial cells in mucosal immunity - Tlaskalová-Hogenová, H; Farré-Castany, M A; Stĕpánková, R; Kozáková, H; Tucková, L; Funda, D P; Barot, R; Cukrowska, B; Sinkora, J; Mandel, L (Folia microbiologica, 1995)
Mucosal surfaces covered by a layer of epithelial cells represent the largest and most critical interface between the organism and its environment. The barrier function of mucosal surfaces is performed by the epithelial layer and immune cells present in the mucosal compartment. As recently found, epithelial cells, apart from their participation in absorptive, digestive and secretory processes perform more than a passive barrier function and are directly involved in immune processes. Besides the well known role of epithelial cells in the transfer of polymeric immunoglobulins produced by lamina propria B lymphocytes to the luminal content of mucosals (secretory Igs), these cells were found to perform various other immunological functions, to interact with other cells of the immune system and to induce an efficient inflammatory response to microbial invasion: enzymic processing of dietary antigens, expression of class I and II MHC antigens, presentation of antigens to lymphocytes, expression of adhesive molecules mediating interaction with intraepithelial lymphocytes and components of extracellular matrix, production of cytokines and probable participation in extrathymic T cell development of intraepithelial lymphocytes. All these functions were suggested to influence substantially the mucosal immune system and its response. Under immunopathological conditions, e.g. during infections and inflammatory bowel and celiac diseases, both epithelial cells and intraepithelial lymphocytes participate substantially in inflammatory reactions. Moreover, enterocytes could become a target of mucosal immune factors. Mucosal immunosurveillance function is of crucial importance in various pathological conditions but especially in the case of the most frequent malignity occurring in the intestinal compartment, i.e. colorectal carcinoma. Proper understanding of the differentiation processes and functions of epithelial cells in interaction with other components of the mucosal immune system is therefore highly desirable.
Keywords: autoimunitní nemoci; epitel; Humans; Fungi; Immunoglobulins; střeva; Integrins; Intestines; cytokiny; střevní sliznice; houby; dospělí; Inflammatory Bowel Diseases; epitelové buňky; lidé; zvířata; myši; lymfoidní tkáň; Membrane Glycoproteins; membránové glykoproteiny; Mice; Autoimmune Diseases; myši knockoutované; Adult; Antigen Presentation; idiopatické střevní záněty; Epithelial Cells; celiakie; kolorektální nádory; Mice, Knockout; Lymphoid Tissue; integriny; Epithelium; Cytokines; Celiac Disease; Bacteria; Animals; Intestinal Mucosa; Peyer's Patches; imunoglobuliny; Colorectal Neoplasms; Peyerovy pláty; prezentace antigenu